Ozone used as a supportive therapy for gingival tissue repair after facial trauma: Report of two cases - Meneses-Santos,Daniela (2021)
Abstract The application of ozone as a supportive therapy has been widely discussed. Ozone has antimicrobial, antioxidant, and healing properties. This study presents two cases of ozone application as a supportive therapy for gingival tissue repair after facial trauma. In both cases, patients suffered extensive lacerations with bone exposure. Tissues were repositioned and sutured; however, ischemia was observed during follow-up with potential tissue necrosis. Each patient received ozone gas with a concentration of 4 μg/ml. Then, the wound was irrigated with 40 mL of ozonated water at a final concentration of 8 μg/ml. The procedure was held weekly until clinical improvement. A significant improvement was observed in ischemia without evolution to necrosis or infection, allowing gingival tissue preservation. Ozone showed a beneficial effect in the recovery of gingiva and alveolar mucosa wounds after extensive trauma.